Nutrition Management in Patients With Chronic Gastrointestinal Motility Disorders: A Systematic Literature Review - Lehmann, Sara; Ferrie, Suzie; Carey, Sharon (Nutrition in clinical practice, 2020)
The aim of this study was to systematically review effects of nutrition interventions on outcomes in patients with chronic gastrointestinal (GI) motility disorders. There is currently a lack of evidence-based guidelines for nutrition management in this group, likely a result of the rarity of the conditions. A systematic review of all study types to evaluate current evidence-based nutrition interventions was performed using Medline, Embase, and CINAHL databases. Two independent reviewers participated in the process of this systematic review. A total of 15 studies and a total of 524 subjects were included. Best treatment of this population group was found to include a stepwise process, progressing from oral nutrition to jejunal nutrition and lastly to parenteral nutrition. Small particle, low-fat diets were significantly better tolerated than the converse, with jejunal nutrition prior to consuming oral food significantly improving oral intake and motility. In more progressive cases, percutaneous endoscopic gastrostomy with jejunal extension nutrition had lower reported symptoms than other enteral routes. Exclusive long-term parenteral nutrition is a feasible option for advanced cases, with a 68% survival rate at 15 years duration, though oral intake with parenteral nutrition is associated with higher survival rates. Treatment of patients with GI motility disorders should first trial oral nutrition. For patients who progress to jejunal or parenteral feeds, the primary aim should be to maintain or reinstate oral intake to reduce morbidity and mortality risk. Higher-quality studies are still required in this area, particularly in the areas of chronic intestinal pseudo-obstruction and systemic sclerosis.